Expanding Engagement Opportunities at a Large Land-Grant Research University: The Engagement Ecosystem Model - Khanjan Mehta; Irena Gorski; Chang Liu; Suzanne Weinstein; Chas Brua; Adam Christensen (The University of Alabama, 2022)
How does a public university with over 80,000 students across 24 campuses provide every student with an engaged scholarship experience? This article chronicles the first steps of this ambitious journey to educate a new generation of engaged scholars by building engagement ecosystems: networks of students, faculty, courses, and communities working together on compelling socially relevant projects around a common theme. By incorporating projects from an impact-focused community engagement program into a cross-section of existing classes, universities can expand engagement opportunities from a select few to the vast majority of the students. This article reviews current approaches to scale engagement opportunities before describing the principles and mechanics of the Engagement Ecosystem model. A case study of the pilot implementation of this model is presented with preliminary assessment results (n=1,165), key lessons learned, and future expansion plans.